2007
DOI: 10.1038/nphoton.2006.80
|View full text |Cite|
|
Sign up to set email alerts
|

A surface-emitting laser incorporating a high-index-contrast subwavelength grating

Abstract: A theoretical study of differences in broadband high-indexcontrast grating (HCG) reflectors for TM and TE polarizations is presented, covering various grating parameters and properties of HCGs. It is shown that the HCG reflectors for TM polarization (TM HCG reflectors) have much thicker grating thicknesses and smaller grating periods than the TE HCG reflectors. This difference is found to originate from the different boundary conditions met for the electric field of each polarization. Due to this difference, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
261
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(267 citation statements)
references
References 22 publications
0
261
0
Order By: Relevance
“…SWG reflectors integrated in Fabry-Perot resonators have also been used to realize vertical-cavity surface-emitting lasers (VCSELs) 19 by replacing the conventional DBRs, and also to show novel MEMS devices. 9,20 This asymmetric Fabry-Perot resonator is equivalent to a conventional Gires-Tournois interferometer, with a bottom mirror exhibiting nearly unity reflectivity and a less reflective top mirror, that is widely used for pulse compression bacause of its highly dispersive phase response.…”
mentioning
confidence: 99%
“…SWG reflectors integrated in Fabry-Perot resonators have also been used to realize vertical-cavity surface-emitting lasers (VCSELs) 19 by replacing the conventional DBRs, and also to show novel MEMS devices. 9,20 This asymmetric Fabry-Perot resonator is equivalent to a conventional Gires-Tournois interferometer, with a bottom mirror exhibiting nearly unity reflectivity and a less reflective top mirror, that is widely used for pulse compression bacause of its highly dispersive phase response.…”
mentioning
confidence: 99%
“…This can be practically realised considering the extraordinary properties of high refractive index contrast gratings (HCGs) Mateus et al (2004a), Mateus et al (2004b). With this approach it is possible to substitute DBR for a heat spreader embodying this kind of structure as a mirror Huang et al (2007), Chang-Hasnain andYang (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the extraordinary and intriguing properties of HCGs have been exploited to design and build various optical elements such as high-Q Fabry-Perot resonators [4], top mirrors in vertical-cavity surface-emitting lasers [5,6], one-and two-dimensional hollow-core low-loss optical waveguides [7], slow-light waveguides [8], planar focusing reflectors and lenses [9,10] In a recent study, we have shown that a two-dimensional HCG structure with optimized geometrical parameters can be utilized for implementing a broadband circular polarizer [18]. The optimized geometrical parameters have been suggested by benefiting from the periodic dielectric slab waveguide interpretation, which is studied rigorously in [19].…”
Section: Introductionmentioning
confidence: 99%